Estudo da Geometria Atômica da Superfície Pt(100)-(1 × 1) - JOÃO VITOR DE OLIVEIRA RIBAS (2025)
This work presents a detailed structural study of the Pt(100)-(1×1) surface using low-energy electron diffraction (LEED). The experiment was conducted at the Synchrotron Light Laboratory - Sirius, at the SAPE experimental station, under ultra-high vacuum conditions. LEED diffraction patterns were collected in the energy range of 30 to 700 eV, with the sample maintained at 322 K and the electron beam at normal incidence. Intensity versus energy I(V) curves were obtained for twenty diffraction beams, which were later reduced to four symmetrically independent beams by averaging the equivalent beams. Structural analysis was performed by comparing theoretical and experimental I(V) curves, using Pendry’s R-factor (Rp) as a quantitative parameter. The final structural model yielded an Rp of 0.3548, consistent with model values found in the literature but exhibiting distinctive features in the interplanar distances: an expansion in d12 (2.12%), a compression in d23 (-2.19%), and an expansion in d34 (2.27%). These results deviate from the typical contraction pattern observed in metals, suggesting the need for further investigations with a broader set of experimental data to achieve a more precise structural determination.